Implementing the SIPAKABERU Application to Enhance Health Services and Nutrition Literacy in Rural Communities - Sendi Pernanda; Auliyah Rofiatul Adawiyah; Cindy Fatika Sari (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2025)
The advancement of digital technology offers significant opportunities to improve community health literacy, particularly in rural areas where access to accurate and comprehensible information remains limited. This community engagement initiative aims to enhance access to health and nutrition information through the implementation of the SIPAKABERU Application, a locally developed digital innovation. The program included socialization activities, application launching, hands-on training for community health volunteers using a learning-by-doing approach, and initial monitoring of user understanding. A total of 63 health volunteers from multiple service areas participated in this program. The results indicate that 81% of volunteers successfully operated the application, although challenges related to limited internet connectivity were identified. The SIPAKABERU Application proved effective in facilitating information dissemination, improving the accuracy of data recording, and encouraging active community engagement. These findings demonstrate that locally developed digital tools can serve as an effective strategy for strengthening health literacy and supporting sustainable community-based health development.